FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP HARGA SAHAM SYARIAH PT. WIJAYA KARYA, TBK., DAN PT. ANEKA TAMBANG, TBK. - Zahida I’tisoma Billah; Nuri Fara Daisil Jinnani (UIN Sunan Gunung Djati Bandung, 2020)
The stock price always changes. Investors can find out the factors that influence it with a fundamental analysis of the company's financial statements. This study aims to determine whether the Return On Assets, Return On Equity, and Debt to Equity Ratio affect the stock price fluctuation of PT. Wijaya Karya, Tbk. and PT. Aneka Tambang, Tbk. in 2016-2018. The research method used is descriptive quantitative, then this study uses the population and samples in the selection of research objects. The population consisted of 30 companies registered in JII, the sampling method was purposive sampling and obtained PT. Wijaya Karya, Tbk. and PT. Aneka Tambang, Tbk. The research data is secondary data obtained from the annual financial reports of the two research samples. The data analysis technique used is multiple regression. The results of the study concluded that both simultaneously and partially ROA, ROE, and DER did not have a significant effect on the stock price of PT. Wijaya Karya, Tbk. and PT. Aneka Tambang, Tbk. 2016-2018 period.